The Waqf of Money as a Community Economic Empowerment Efforts - Diana Farid (International Journal of Nusantara Islam, 2016)
Waqaf is basically seen as one of the religious institutions in Islam which is relevant and functionally efforts to solve socio-economic problems and humanity, such as poverty alleviation, human resource development, and economic empowerment. The endowments are absolutely an important role in achieving a just social order. From the perspective of shapes, endowment money is seen as one of the solutions that can make endowments to be more productive. Because the money here will no longer to be used as a means of exchange, but more than it, we can explore it as a commodity to produce in the terms of economic development. Therefore, the cash money in the form of waqaf of money can result any benefit for the community. Appearances distribution of endowments can be used to productive activity in the era of economic downturn of the Islamic community in Indonesia. Now it should become the primary choice. In another sense, it is a productive waqaf endowment that must be a priority and dedicated its efforts to more fruitful. Thus, the sizes of different paradigms are done by the consumptive waqaf, because it gives a new hope for the majority of the Muslim community. Endowments are not willing to lead in worship of mahdhah which is directed to the consumptive waqaf. Using the findings of waqaf has been prioritized to give benefit in a very broad, including for economic empowerment, such as public facilities and worship activities, social facilities and educational activities as well as health, aid to poor people, displaced children, orphans, scholarship, progress and economic improvement for the people who needs the advancement of public welfare other non-contrary to the sharia business law.